The Study of Different Outcome in the Observational Care of Mild Traumatic Brain Injury with Moderate Risk for Intracranial Bleeding at Short Stay Unit and In-patient Ward, Phra Nakhon Si Ayutthaya Hospital - บุณยะวิโรจ สรสิทธิ์ (Journal of Preventive Medicine Association of Thailand, 2018)
The retrospective cohort study reviews 388 patients with mild traumatic brain injury with moderate risk for intracranial bleeding at short stay unit and in-patient ward, Phra Nakhon Si Ayutthaya Hospital. Multiple patient related factors were studied such as general characteristics, mechanisms of injuries, symptoms and signs, radiological examinations, observations and treatment for each group. The result shows multiple factors have statistically significant difference such as precision of treatment, accident and fall in cause of injuries, periods of visits, and etc. Multivariable Gaussian Regression shows statistically significances in two groups of patients who comeback to visit without appointments.